Relationship between fluoride exposure and count of Streptococcus mutans in supragingival biofilm of mexican scholar children - B. Holguin-Loya; U. Soto-Barreras; R. Martinez-Martinez; G. Martinez-Mata; L. Sanin; M. Nevarez-Rascon; R. Dominguez-Perez (Elsevier, 2022)
Background/purpose: The use of fluoride is known to reduce the risk of dental caries. There is limited information on the relationship between Streptococcus mutans (S. mutans) and fluoride exposure. This study investigated the association between the count of S. mutans on supragingival biofilm and fluoride exposure of scholar children. Materials and methods: In this cross-sectional study, 56 children from 9 to 11 years of age were selected. Fluoride concentration in drinking water, urine and saliva of each participant were assessed. The count of S. mutans was estimated by calculating the DNA copy number through a quantitative real time polymerase chain reaction (qPCR) assay. Also, sociodemographic data, oral and general health information and variables related to caries risk were evaluated. A stepwise multiple linear regression was performed in all caries related predictor variables with the count of S. mutans as the dependent variable. Results: The multiple linear regression analysis showed that the concentration of fluoride in saliva (β = −3.029, p < 0.001) and urine (β = −2.057, p = 0.017), time of last visit to the dentist (β = 1.968, p = 0.001), plaque index (β = 1.637, p = 0.006) and number of surfaces with codes 3-6 (D3-6MFS) of ICDAS II criteria (β = 0.283, p = 0.076) were significantly associated with the count of S. mutans (Adjusted R square = 0.427, p < 0.001). Conclusion: Fluoride levels in urine and saliva were negatively associated with the count of S. mutans in supragingival biofilm. Plaque index, D3-6MFS and time of last visit to the dentist showed a positive association.